2013
DOI: 10.1002/bit.24834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cultivation conditions on N‐glycosylation of influenza virus a hemagglutinin produced in MDCK cell culture

Abstract: Manufacturers worldwide produce influenza vaccines in different host systems. So far, either fertilized chicken eggs or mammalian cell lines are used. In all these vaccines, hemagglutinin (HA) and neuraminidase are the major components. Both are highly abundant glycoproteins in the viral envelope, and particularly HA is able to induce a strong and protective immune response. The quality characteristics of glycoproteins, such as specific activity, antigenicity, immunogenicity, binding avidity, and receptor-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 68 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…HMOS concentration changes during lactation were analyzed by calculating relative PHP (as published previously for N-glycosylation patterns [92,[98][99][100][101][102][103]). Briefly, the same set of 18 peaks was picked in all HMOS fingerprints of the samples from the LTP series (peak picking criteria: peaks > 200 relative fluorescence units (RFU) or already known peaks).…”
Section: Quantitative Comparison Of Hmos Fingerprints At Different Lamentioning
confidence: 99%
“…HMOS concentration changes during lactation were analyzed by calculating relative PHP (as published previously for N-glycosylation patterns [92,[98][99][100][101][102][103]). Briefly, the same set of 18 peaks was picked in all HMOS fingerprints of the samples from the LTP series (peak picking criteria: peaks > 200 relative fluorescence units (RFU) or already known peaks).…”
Section: Quantitative Comparison Of Hmos Fingerprints At Different Lamentioning
confidence: 99%
“…Besides the buffer conditions, e.g., pH value, ionic strength, osmolarity, and the presence of excipients [2,3], the structural characteristics of VP surface proteins, e.g., mutations or glycosylation strongly influence the aggregation propensity [7]. It has already been shown that the N-glycosylation of the influenza A virus surface protein hemagglutinin (HA) depends strongly on the host cell line [8][9][10][11], which might change the physicochemical properties of the whole VP. In a previous study [12] we investigated ion-specific effects on the particle size distributions and aggregation of influenza A (A/Puerto Rico/8/34 H1N1, A/PR) VP produced in adherent and suspension Madin Darby canine kidney (MDCK) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies regarding the adaptation of MDCK cells to suspension growth revealed a clear impact on cellular physiology and influenza virus replication, i.e. changes in glycosylation and onset of apoptosis were observed. In particular, suspension cells showed an earlier induction of apoptosis and a decreased cell‐specific virus yield .…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the physiological status of cells after adaptation can have a significant impact, not only on growth properties and process robustness, but also on virus replication. For the MDCK suspension cell line established recently (MDCK SUS2 ) , it was shown that adaptation also influences the glycosylation of 0hemagglutinin (HA) , the main immunogenic membrane protein of influenza A virus. Additionally, differences for MDCK ADH and MDCK SUS2 cells were observed regarding the onset of virus‐induced cell death determined by late apoptosis markers (DNA fragmentation) .…”
Section: Introductionmentioning
confidence: 99%